Stroke-Like Episodes in PMM2-CDG: When the Lack of Other Evidence Is the Only Evidence - Serrano, Mercedes (Frontiers in Pediatrics, 2021)
Phosphomannomutase 2 deficiency (PMM2-CDG) is the most frequent congenital disorder of glycosylation. PMM2-CDG patients develop chronic cerebellar atrophy as a neurological hallmark. However, other acute neurological phenomena such as stroke-like episodes (SLE), epilepsy, migraine, and cerebrovascular events, may also occur, and they are frequently the cause of disability and impaired quality of life. Among these, SLE are among the most stressful situations for families and doctors, as their risk factors are not known, their underlying pathomechanisms remain undiscovered, and clinical guidelines for diagnosis, prevention, and treatment are lacking. In this paper, the recent SLE experiences of two PMM2-CDG patients are examined to provide clinical clues to help improve diagnosis through a clinical constellation of symptoms and a clinical definition, but also to support a neuroelectrical hypothesis as an underlying mechanism. An up-to-date literature review will help to identify evidence-based and non-evidence-based management recommendations. Presently neuropediatricians and neurologists are not capable of diagnosing stroke-like episodes in an unequivocal way, so there is still a need to perform invasive studies (to rule out other acute diseases) that may, in the end, prove unnecessary or even harmful. However, reaching a correct and early diagnosis would lead not only to avoidance of invasive tests but also to better recognition, management, and understanding of the disease itself. There is a great need for understanding of SLE that may ultimately be very informative for the detection of patients at risk, and the future development of preventive and management measures.